Research and Modeling of the Bidirectional Half-Bridge Current-Doubler DC/DC Converter - Liang Huang; Xinchao Dong; Changjun Xie; Shuhai Quan; Yang Gao (International Journal of Rotating Machinery)
Due to its high step-up voltage ratio, high utilization rate, and good stability, the bidirectional half-bridge current-doubler topology is widely used in lithium battery system. This paper will further analyze the bidirectional half-bridge current-doubler topology. Taking into account the fact that the current is not equal to the two times current inductance may lead to a greater transformer magnetizing current leaving the transformer core saturation occurring. This paper will focus on the circuit modeling of steady-state analysis and small signal analysis, analyzing the influence parameters for the inductor current by steady-state model and analyzing the stability of the system by the small signal model. The PID controllers and soft start algorithm are designed. Then the influence of circuit parameters on the steady state and the effect of soft start algorithm is verified, and finally the function of the soft start algorithm is achieved by the experimental prototype.